Day 3 Thu, December 01, 2022 2022
DOI: 10.2118/212152-ms
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Decision-Making Strategy for Thermal Well Completion

Abstract: Various wellbore completion strategies have been developed for thermal wells in Western Canada. The idea in this paper is estimating the improvement of oil production and steam injection if flow control devices (FCDs) will be installed for the next wells to be drilled, or if FCDs were installed at a particular well-pad that has not yet been completed with any FCDs. The approach is based on labeled real data for 68 well-pads from seven major thermal projects in Western Canada. Three phases make u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the data-driven analysis performed in this study and results reported by ref , LDICDs performed better in increasing oil production and lowering cSOR than TDICDs. One reason could be the risk of failure associated with TDICD completion as a result of sand production if the well completed by TDICDs is run by the same subcool and production rate as that completed by LDICDs . In this paper, the subcool and good operational parameters remained the same for both cases with LDICDs and TDICDs, and still, the case with LDICDs performed better than the case with TDICDs.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In the data-driven analysis performed in this study and results reported by ref , LDICDs performed better in increasing oil production and lowering cSOR than TDICDs. One reason could be the risk of failure associated with TDICD completion as a result of sand production if the well completed by TDICDs is run by the same subcool and production rate as that completed by LDICDs . In this paper, the subcool and good operational parameters remained the same for both cases with LDICDs and TDICDs, and still, the case with LDICDs performed better than the case with TDICDs.…”
Section: Resultsmentioning
confidence: 61%
“…One reason could be the risk of failure associated with TDICD completion as a result of sand production if the well completed by TDICDs is run by the same subcool and production rate as that completed by LDICDs. 51 In this paper, the subcool and good operational parameters remained the same for both cases with LDICDs and TDICDs, and still, the case with LDICDs performed better than the case with TDICDs. We concluded that this is because LDICDs are in direct contact with the sand face; therefore, they can provide the pressure drop more efficiently, resulting in a more equalized fluid rate entering the well (Figure 31).…”
Section: Discussion and Limitationsmentioning
confidence: 56%